Sports compression garments improve resting markers of venous return and muscle blood flow in male basketball players - Shane F. O'Riordan; Rod McGregor; Shona L. Halson; David J. Bishop; James R. Broatch (Elsevier, 2023)
Background: The benefits associated with sports compression garments are thought to be closely related to enhanced blood flow. However, findings are equivocal, possibly due to heterogeneity in the techniques used for measuring blood flow, the garment types used, and the pressures applied. This study combined Doppler ultrasound and near-infrared spectroscopy technologies to provide the first comprehensive assessment of the effects of 3 sports compression garment types on markers of venous return and muscle blood flow at rest. Methods: Resting lower-limb blood flow measures (markers of venous return, muscle blood flow, and muscle oxygenation) of 22 elite, junior, male basketball players (age = 17.2 ± 0.9 years, mean ± SD) were assessed in 4 separate conditions: no compression (CON), compression tights (TIGHTS), compression shorts (SHORTS), and compression socks (SOCKS). Markers of venous return (cross-sectional area, time-averaged mean and peak blood flow velocity, and venous blood flow) were measured via Doppler ultrasound at the popliteal and common femoral veins. Muscle blood flow and muscle oxygenation were measured in the gastrocnemius medialis and vastus lateralis using near-infrared spectroscopy. Results: Popliteal markers of venous return were higher in TIGHTS compared to CON (p < 0.01) and SHORTS (p < 0.01), with SOCKS values higher compared with CON (p < 0.05). Common femoral vein markers of venous return were higher for all conditions compared to CON (p < 0.05), with TIGHTS values also higher compared to SOCKS (p < 0.05). Gastrocnemius medialis blood flow was higher for TIGHTS compared to CON (p = 0.000), SOCKS (p = 0.012), and SHORTS (p = 0.000), with SOCKS higher compared to SHORTS (p = 0.046). Vastus lateralis blood flow was higher for TIGHTS compared to CON (p = 0.028) and SOCKS (p = 0.019), with SHORTS also higher compared to CON (p = 0.012) and SOCKS (p = 0.005). Gastrocnemius medialis oxygenation was higher for TIGHTS compared to CON (p = 0.003), SOCKS (p = 0.033), and SHORTS (p = 0.003), with SOCKS higher compared to CON (p = 0.044) and SHORTS (p = 0.032). Vastus lateralis oxygenation was higher for TIGHTS compared to CON (p = 0.020) and SOCKS (p = 0.006). Conclusion: Markers of venous return, muscle blood flow, and muscle oxygenation are increased with sports compression garments. TIGHTS are most effective, potentially because of the larger body area compressed.